Pengembangan Lembar Kegiatan Peserta Didik Berbasis Kearifan Lokal Batik Bojonegoro Untuk Meningkatkan Keterampilan Berpikir Kreatif Dan Pemecahan Masalah IPS Kelas IV Sekolah Dasar - Ratna Nurma Yunita; Mustaji; Rr. Nanik Setyowati (LP. Ma'arif Janggan Magetan, 2022)
This study aims to: (1) test the feasibility of LKPD based on local wisdom of Bojonegoro batik for fourth grade students at SD Negeri Grebegan Bojonegoro, (2) testing the practicality of LKPD based on local wisdom of Bojonegoro batik as a support material for the beauty of diversity in my country on the theme of 7th grade IV SD, (3) testing the effectiveness of LKPD based on local wisdom of Bojonegoro batik to improve creative thinking skills on theme 7th grade IV SD, (4) testing the effectiveness of LKPD based on local wisdom of Bojonegoro batik to improve problem solving ability on theme 7 grade IV SD. This learning media development research refers to the ADDIE model. The subjects of the study were fourth grade students of SD Negeri Grebegan with a total of 28 children. This research design uses One-Shot Case Study to measure creative thinking ability and One-Group Pretest-Posttest to measure problem solving ability. The results of this study indicate (1) that the learning device in the form of a syllabus obtained a validation result of 85.71% and was included in the